The association between prostate cancer and mood disorders: a nationwide population-based study in Taiwan. (22nd October 2014) - Chen, Pan-Ming; Chen, San-Chi; Liu, Chia-Jen; Hung, Man-Hsin; Tsai, Chia-Fen; Hu, Yu-Wen; Chen, Mu-Hong; Shen, Cheng-Che; Su, Tung-Ping; Yeh, Chiu-Mei; Lu, Ti; Chen, Tzeng-Ji; et al.
ABSTRACT: Background: This study identified possible risk factors for newly diagnosed mood disorders, including depressive and bipolar disorders, in prostate cancer patients. Methods: From 2000 to 2006, two cohorts were evaluated on the occurrence of mood disorder diagnosis and treatment. For the first cohort, data of patients diagnosed with prostate cancer was obtained from the Taiwan National Health Insurance (NHI) Research Database. As the second cohort, a cancer-free comparison group was matched for age, comorbidities, geographic region, and socioeconomic status. Results: Final analyses involved 12, 872 men with prostate cancer and 12, 872 matched patients. Increased incidence of both depressive (IRR 1.52, 95% CI 1.30–1.79, P <0.001) and bipolar disorder (IRR 1.84, 95% CI 1.25–2.74, P = 0.001) was observed among patients diagnosed with prostate cancer. Multivariate matched regression models show that cerebrovascular disease (CVD) and radiotherapy treatment could be independent risk factors for developing subsequent depressive and bipolar disorders. Conclusion: We observed that the risk of developing newly diagnosed depressive and bipolar disorders is higher among Taiwanese prostate cancer patients. Clinicians should be aware of the possibility of increased depressive and bipolar disorders among prostate cancer patients in Taiwan. A prospective study is necessary to confirm these findings.